Calculating Calf Performance in Beef Operations: The University of Florida Beef Herds in the 2019–2020 Calving Season - Mario Binelli; Angela Maria Gonella-Diaza; Thiago Martins; Cecilia Constantino Rocha; Felipe Alves Correa Carvalho Silva; Federico Tarnonsky; Sergio Daniel Roskopf; Owen Rae; Joseph Daniel Driver; Nicolas DiLorenzo; Jose Carlos Dubeux; David Thomas (EDIS)
This article aims to report the calf performance of two beef herds of the University of Florida, located in north (UF/IFAS NFREC, Marianna) and central Florida (Beef Units, Gainesville). Written by Mario Binelli, Angela M. Gonella-Diaza, Thiago Martins, Cecilia C. Rocha, Felipe A. C. C. Silva, Federico Tarnonsky, Sergio Roskopf, Owen Rae, Danny Driver, Nicolas DiLorenzo, Jose Dubeux, and David Thomas, and published by the UF/IFAS Department of Animal Sciences, February 2022.